Book Reviews. (1st June 2015) - Anderson, Peter; Kent, Charlotte; Geoghegan, Chloe; Mutlu, Rasit
HOW TO WRITE ABOUT CONTEMPORARY ART, GILDA WILLIAMS London: Thames and Hudson (2014), 264 pp., Paperback, ISBN: 978-0-50029-157-3, £12.95CAPITAL CULTURE: J. CARTER BROWN, THE NATIONAL GALLERY, AND THE REINVENTION OF THE MUSEUM EXPERIENCE, NEIL HARRIS Chicago and London: University of Chicago Press (2013), 616 pp., Hardcover, ISBN: 978-0-22606-770-4, US$35.00INSTITUTIONS BY ARTISTS: VOLUME ONE, JEFF KHONSARY AND KRISTINA LEE PODESVA (EDS) Vancouver: Fillip Editions and Pacific Association of Artist Run Centres (2012), 384 pp., Paperback, ISBN: 978-1-92735-402-5, CAN$20.00YOU ARE HERE: ART AFTER THE INTERNET, OMAR KHOLEIF (ED.) Manchester and London: Cornerhouse and SPACE (2014), 256 pp., ISBN: 978-0-95695-717-7, Paperback, £15.95